Announcement effect of macroeconomic indicators on the U.S. dollar/Canadian dollar exchange rate. - Cheu, Lai Peng. (2008)
This paper employs event methodology to investigate the impact of inflation, national output and money supply announcements on the U.S. dollar/Canadian dollar exchange rate from 1996 to 2000.